Long-term outcomes of pancreatoscopy-guided electrohydraulic lithotripsy for the treatment of obstructive pancreatic duct stones - de Rijk, Florence E.M.; Stassen, Pauline M.C.; van der Wiel, Sophia E.; Boermeester, Marja A.; Issa, Yama; Kempeneers, Marinus A.; Verdonk, Robert C.; Bruno, Marco J.; de Jonge, Pieter Jan F. (Endoscopy International Open, 2023)
Background and study aims Pancreatoscopy-guided electrohydraulic lithotripsy (EHL) has proven to be an effective first-line therapy in symptomatic chronic pancreatitis (CP) patients with obstructing pancreatic duct (PD) stones 1. However, long-term outcomes of endoscopic EHL remain unknown. The aim of the present study was to evaluate the long-term treatment effects of EHL as first-line therapy and to compare with those obtained in a historical cohort of patients who underwent extracorporeal shockwave lithotripsy (ESWL) as primary treatment.Patients and methods An observational retrospective single-center long-term follow-up study was performed including 19 consecutive patients who previously underwent endoscopic EHL compared to 18 patients who underwent ESWL followed by endoscopic retrograde pancreatography (ERP). The primary endpoint was long-term treatment success after EHL or ESWL defined as no recurrence of symptomatic intraductal stones confirmed on imaging. Secondary endpoints for the EHL-population included long-term clinical success (i. e., a similar or lower Izbicki Pain Score or reduction in opiate usage as compared to 6-month follow-up), quality of life (QoL), pancreatic function and hospital re-admission rate.Results In the EHL group, 37 % of the patients developed recurrent symptomatic PD stones versus 61 % in the ESWL group after a median follow-up of 35.0 and 76.5 months. Of the patients with recurrence, 71 % versus 100 % underwent a reintervention. Median time to recurrence was 12.0 versus 13.0 months. Clinical success sustained in 58 % of the EHL patients. QoL was not significantly different compared with 6-month follow-up and baseline.Conclusions Also at long-term follow-up, endoscopic EHL as first-line treatment is moderately effective for symptomatic CP patients with treatment success rates that seems at least equally effective as ESWL.